ULTRAFAST OCEANIC SPREADING OF THE MARSILI BASIN, SOUTHERN TYRRHENIAN SEA: EVIDENCE FROM MAGNETIC ANOMALY ANALYSIS - Nicolosi I.; Speranza F.; Chiappini M. (My University, 2006)
Spectral analysis of both shipborne and airborne magnetic maps of the southern Tyrrhenian Sea reveals seven subparallel positive-negative magnetic anomaly stripes over the flat-lying deep floor of the Marsili oceanic basin. This represents the first evidence of oceanic magnetic anomalies in the Tyrrhenian Sea. The central positive stripe is along the Marsili seamount, a superinflated spreading ridge located at the basin axis. The stratigraphy of Ocean Drilling Program Site 650 and K/Ar ages from the Marsili seamount suggest that the Marsili Basin opened at the remarkable full-spreading rate of ~19 cm/yr between ca. 1.6 and 2.1 Ma about the Olduvai subchron. This is the highest spreading rate ever documented, including that observed at the Cocos-Pacific plate boundary. Renewed but slow spreading during the Brunhes chron (after 0.78 Ma), coupled with huge magmatic inflation, gave rise to the Marsili volcano. Our new data and interpretation show that backarc spreading of the Tyrrhenian Sea was episodic, with sudden rapid pulses punctuating relatively long periods of tectonic quiescence. © 2006 Geological Society of America.
Keywords: MAGNETIC ANOMALIES; MARSILI BASIN; OCEAN SPREADING; TYRRHENIAN SEA